2013
DOI: 10.1128/jb.00279-13
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Physiological Responses of Bifidobacterium animalis subsp. lactis to Hydrogen Peroxide Stress

Abstract: bConsumer interest in probiotic bifidobacteria is increasing, but industry efforts to secure high cell viability in foods is undermined by these anaerobes' sensitivity to oxidative stress. To address this limitation, we investigated genetic and physiological responses of two fully sequenced Bifidobacterium animalis subsp. lactis strains, BL-04 and DSM 10140, to hydrogen peroxide (H 2 O 2 ) stress. Although the genome sequences for these strains are highly clonal, prior work showed that they differ in both intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…Since LA exposure influenced genes and regulators involved in lipid metabolism, one could speculate that the cell membrane might be a target of LA action. Previous studies demonstrate that several kinds of stresses, including osmotic or acid stress, can prompt modifications in the bacterial cell membrane composition-particularly fatty acid chain length, saturation, and cyclopropanation-to decrease membrane permeability to oxidative free radicals and increase membrane resistance to lipid peroxidation [51]. We observed that LA induced downregulation of genes, such as the TadE gene, encoding type IVb tight adherence pili, which is in accordance with another transcriptional analysis showing reduced expression of these genes in response to stress conditions [52].…”
Section: Discussionmentioning
confidence: 99%
“…Since LA exposure influenced genes and regulators involved in lipid metabolism, one could speculate that the cell membrane might be a target of LA action. Previous studies demonstrate that several kinds of stresses, including osmotic or acid stress, can prompt modifications in the bacterial cell membrane composition-particularly fatty acid chain length, saturation, and cyclopropanation-to decrease membrane permeability to oxidative free radicals and increase membrane resistance to lipid peroxidation [51]. We observed that LA induced downregulation of genes, such as the TadE gene, encoding type IVb tight adherence pili, which is in accordance with another transcriptional analysis showing reduced expression of these genes in response to stress conditions [52].…”
Section: Discussionmentioning
confidence: 99%
“…RNA isolation was performed as previously described (Oberg et al, 2013). Cells were grown in batch culture under pH control to early stationary phase and then samples (5 mL) were harvested by centrifugation at 7500 × g for 10 min.…”
Section: Rna Isolationmentioning
confidence: 99%
“…cDNA synthesis and labeling was performed as described previously (Oberg et al, 2013). cDNA was synthesized and labeled as recommended by the Affymetrix (Santa Clara, CA) protocol for prokaryotic target preparation in the GeneChip Expression Analysis Technical Manual (media.affymetrix.com).…”
Section: Synthesis and Labeling Of Cdnamentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivation of lactic acid bacteria and Bifidobacteria has been the subject of numerous studies considering their importance as probiotics [17,21,24,26]. Besides this application, some specific strains of Bifidobacteria are also becoming popular as functional foods [19].…”
Section: Introductionmentioning
confidence: 99%